Who Must Pay Bribes and How Much? Evidence from a Cross-Section of Firms - Svensson, Jakob (World Bank, Washington, DC, 2014)
The author exploits a unique data set on corruption containing information about estimated bribe payments by Ugandan firms. To guide the empirical analysis, he develops a simple rent-extortion model, which yields predictions on both the incidence of bribery, and the amount paid. Both predictions are consistent with the data. Firms typically have to pay bribes when dealing with public officials whose actions directly affect the firms' business operations. And the amount paid in bribes is not a fixed sum for a set of public services, but depends on the firm's ability to pay. Controlling for other potential explanations of the relationship between "ability to pay" and equilibrium graft, the author shows that the more a firm can pay, the more it has to pay.